Media społecznościowe w e-learningu akademickim - Ordon, Urszula; Sołtysiak, Wioletta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
W artykule dokonano próby zaakcentowania ważności mediów społecznościowych jako instrumentu w komunikacji interpersonalnej przyjaznego uczestnikom kształcenia w szkole wyższej realizującej e-learningowy model. W tym celu odwołano się do badań przeprowadzonych wśród studentów uczelni ekonomicznych.

The article is an attempt to stress importance of social media as an instrument in interpersonal communication, friendly for participants of the education process at a university implementing an e-learning education model. For this purpose, a reference was made to research carried out among students of economic universities.
Social Media in Academic e-Learning
Keywords: e-learning; kształcenie; social media; education